Psychology of Characters in the Novel Cahaya Palestine by Vanny CW (Review of Literary Psychology) - Najamudin, Najamudin; Sukarismanti, Sukarismanti; Hairat, Hairat (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study aims to describe the psychology (personality) of the characters in the novel Cahaya Palestine by Vanny C.W. This type of research is descriptive qualitative research, the data collection methods used in this research are library research, reading methods, listening and recording data identification. The source of the data in this study was the novel Cahaya Palestine by Vanny C.W. This study uses Sigmund Freud's psychoanalytic theory in the form of id, ego and superego in figures named Palestine, Yanaan, Yahded Haidar, Abigail, Moniroth, Hebrew, Sarah Hanabi, Fatima, Khalifa Al Barra and Adeeda. The results of this study are the figures of Palestine, Yanaan, Yahded Haidar, Abigail, Moniroth, Hebrew, Sarah Hanabi, Fatima, Khalifa Al Barra and Adeeba who have psychology that refers to Sigmund Freud's theory namely, id, ego and superego.